Современная практика планирования и подготовки проектно-технологической документации проектов строительной отрасли - Тімощук, Д. В.; Іщенко, О. С. (Ways to Improve Construction Efficiency, 2012)
The paper analyzed necessity of developing an improved process of organizational and technological planning stage of design documentation of the POB and PPW. Presented: a generalized scheduling algorithm of the construction project, the composition and development scheme design and technological documentation, substantiation of the basic design decisions of organizational and technological design.